Modelling and analysis of the dynamic response of a railway viaduct using an accurate and efficient algorithm. (1st January 2021) - Neves, S.G.M.; Montenegro, P.A.; Jorge, P.F.M.; Calçada, R.; Azevedo, A.F.M.
Highlights: A novel, accurate and efficient vehicle-structure interaction algorithm is used. Optimisation of the mesh size significantly decreased the computational cost. Studies how track isolated defects influence the dynamic behaviour of a viaduct. Shape of the defect and local deformations of the slab have a strong influence. Standards do not account for the defect shape or local deformations of the slab. Abstract: This article describes the simulation of the Korean high-speed train passing over a single-track viaduct and the influence of track isolated defects on the dynamic behaviour of the system. The model of the viaduct is validated and calibrated using a finite element model updating technique, and a three-dimensional (3D) model is used to account for the local deformations of the slab accurately. The direct method, an efficient vehicle-structure interaction algorithm previously developed by the authors, is used to solve the dynamic problem. It proved to be significantly more efficient than the widely used finite element software ANSYS® when solving large and complex problems. The computational time has been reduced by more than ten times. The results obtained show that the shape of the isolated defects and the local deformations of the slab strongly influence the dynamic behaviour of the system. Neither is taken into account in the current standards, and hence further research is necessary.